2020
DOI: 10.1002/jcsm.12545
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D on sarcopenia depends on the level of physical activity in older adults

Abstract: Objective Sarcopenia in older adults is closely related to vitamin D deficiency and reduced levels of physical activity, but little has been reported on the interaction between physical activity and the positive effects of vitamin D. The purpose of this study was to explore the interactive effect of vitamin D and physical activity on muscle mass and function through animal experiments and population surveys. Methods Male 4‐week‐old C57BL/6J mice were fed different purified diets: a vitamin D‐deficient diet (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 58 publications
3
38
0
2
Order By: Relevance
“…Moreover, 1,25(OH) 2 D suppressed the increased expression of atrogin-1 and cathepsin L, target genes for FOXO1, which induces muscle atrophy in C2C12 myoblasts [ 59 ] ( Figure 2 ). Interestingly, Yang et al recently reported that physical inactivity and low serum vitamin D can synergistically promote sarcopenia in the elderly [ 60 ]. Under inactive conditions, vitamin D deficiency accelerated the loss of muscle mass, muscle cross-sectional area, and grip strength, and conversely increased protein expression of FOXO3a and its target genes (Atrogin-1 and MuRF1).…”
Section: Mechanism Of Action Of Vitamin D On Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 1,25(OH) 2 D suppressed the increased expression of atrogin-1 and cathepsin L, target genes for FOXO1, which induces muscle atrophy in C2C12 myoblasts [ 59 ] ( Figure 2 ). Interestingly, Yang et al recently reported that physical inactivity and low serum vitamin D can synergistically promote sarcopenia in the elderly [ 60 ]. Under inactive conditions, vitamin D deficiency accelerated the loss of muscle mass, muscle cross-sectional area, and grip strength, and conversely increased protein expression of FOXO3a and its target genes (Atrogin-1 and MuRF1).…”
Section: Mechanism Of Action Of Vitamin D On Skeletal Musclementioning
confidence: 99%
“…Under inactive conditions, vitamin D deficiency accelerated the loss of muscle mass, muscle cross-sectional area, and grip strength, and conversely increased protein expression of FOXO3a and its target genes (Atrogin-1 and MuRF1). In older adults, serum 25 (OH) D 3 and physical activity showed interactive effects on physical performance (timed up and go test) and muscle strength (grip strength) [ 60 ].…”
Section: Mechanism Of Action Of Vitamin D On Skeletal Musclementioning
confidence: 99%
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“…Of the nutrition studies that we found, one explored the role of protein, 31 three explored the role of vitamin D, 26,38,39 two explored the role of several nutrients, 3,41 and one explored the role of natural product (astaxanthin) supplements 40 . Seven studies 25,27–30,32,33 investigated the effects of multimodal interventions (defined as two or more approaches) on muscle mass.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“…10,[19][20][21][22] In addition, sarcopenia is associated with falls and fractures among older adults, with elevated risk of mortality, given the effect of vitamin D on muscle strength and physical performance, which depend on the PA level demonstrated by elderly people. 4,23 Nevertheless, only a few studies have focused on the relationship between sarcopenia and physical activity levels in the geriatric population, especially with regard to clinical variables relating to the diagnosis of sarcopenia, such as physical performance, handgrip strength and balance. In a cross-sectional study on community-dwelling older adults in Korea, it was found that moderate-to-vigorous physical activity was associated with a reduced risk of sarcopenia.…”
mentioning
confidence: 99%